The Development of Extracurricular Activities in The Curriculum of Islamic Religious Education and Character in School in Society 5.0 - Sukiman (Proceeding International Conference on Religion, Science and Education, 2022)
Islamic Religious Education and Character in schools must continue to be developed to contribute to the thoughts and personalities of the younger generation in responding to the challenges of the 5.0 era of society. However, in reality, the achievements and competencies of learners in educational institutions in PAI and Character today generally have not reached an encouraging level of competence. Therefore, it is necessary to develop PAI and Character learning activities in school. The form of development is to strengthen extracurricular activities so that the goals and competencies of PAI and Character can be achieved according to the expected standards. The learning process of PAI and Character in schools is not enough if it is only given through intracurricular programs but must be strengthened through religious and technology-based extracurricular programs so that the goals and competencies of PAI can be achieved according to the expected standards. PAI teachers must strive for Islamic behavior in students through two religious activities, namely intracurricular activities and extracurricular activities. This article uses a library research method. This research uses a rationalistic thinking foundation—data collection using documentation techniques. Sources of research data come from library materials in the form of curriculum documents for Islamic Religious Education and Morals, regulations and policies regarding implementing extracurricular activities in schools, books, journal articles, and research results on extracurricular activities in schools. The data analysis technique uses critical text analysis. This article details the development of PAI and Character extracurricular activities in schools. Topics to be discussed include the basic concepts of extracurricular activities, foundations, approaches of implementing extracurricular activities, forms of extracurricular activities, and the assessment of PAI and Character extracurricular activities in schools.